Comparison of suture-based and collagen-based vascular closure devices for large bore arteriotomies- an updated meta-analysis of bleeding and vascular complications. (14th October 2021) - Sohal, S S; Kurpad, K K; Kaur, K K; Wasty, N W; Tayal, R T
Abstract: Background: Large bore access procedures such as transcatheter aortic valve replacement or mechanical circulatory support devices rely on percutaneous vascular closure devices to minimize access site complications. Suture-based vascular closure devices (S-VCD) have been readily used but recently newer generation collagen-based vascular closure devices (C-VCD) have been introduced to ensure minimally invasive nature of large bore devices and prevent vascular and bleeding complications at the access site. However, large population data on outcomes of these devices is lacking. Purpose: To compare the bleeding and vascular complications of suture-based and collagen- based vascular closure devices for large bore access. Methods: PubMed was searched for articles on vascular closure devices using keywords, ("Vascular closure devices") AND ("bleeding OR vascular complications") that resulted in a total of 456 studies. Studies were included if bleeding or vascular complications as defined by Valve Academic Research Consortium-2 (VARC-2) were compared between the two types of VCDs. 6 (5 observational and 1 Randomized controlled trial) studies met the inclusion criteria. The event level data was pooled across trials to calculate Odds Ratio (OR) with 95% CI and analysis was done using Review Manager 5.4 (RevMan 5.4). Random effect model was used in RevMan 5.4 for the analysis and p value of <0.05 was deemed significant. Results: Pooled analyses from these 6 trials resulted in a total of 1, 307 patients, out of which 550 received C-VCD and 757 received S- VCD. Among the patients who received C-VCD, the bleeding complications (major and minor) were non significantly lower than in patients who received S-VCD ((OR: 0.71 (0.33–1.53), p=0.38, I 2 =47%), (OR: 0.78 (0.40–1.50), p=0.45, I 2 =52%)). The vascular complications (major and minor) in patients who received C-VCD were similar to patients who received S-VCD ((OR: 0.85 (0.47–1.54), p=0.59, I 2 =0%), (OR: 0.92 (0.38–2.22), p=0.86, I 2 =37%)) (Picture 1 and Picture 2). Conclusions: Bleeding and vascular complications after large bore arteriotomy closure with collagen based vascular closure devices are similar to suture based vascular closure devices. Therefore, collagen-based devices seem to be a feasible option to obtain hemostasis in large bore arteriotomies without increasing risk for vascular complications. Funding Acknowledgement: Type of funding sources: None.